Pengaruh Metode Pembelajaran Mimicry Memorization Terhadap Motivasi dan Hasil Belajar Bahasa Arab - Khasanah, Uswatun; Faizah, Silviana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research is motivated by the need for more innovative and effective Arabic language learning methods. The purpose of this study was to determine the effect of the Mimicry Memorization (MIM-MEM) method on Arabic language learning motivation and outcomes. This study is a quantitative study with a quasi-experimental method. The experimental design used was pretest and posttest in one group. Data collection techniques used tests, questionnaires, and documentation. Data analysis techniques used descriptive and inferential statistical techniques. Descriptive statistical techniques were carried out by analyzing the average score and N-Gain. Inferential techniques were carried out by testing the hypothesis using a paired sample t-test. The results showed that the average student learning motivation increased by 37.17 with an N-Gain of 0.42 which was in the moderate category and an increase in the average student learning outcomes was obtained by 40.67 with an N-Gain of 0.43 which was in the moderate category. The results of the hypothesis test of motivation and learning outcomes data obtained the same significance value, namely 0.000 (<0.05) which indicated that the alternative hypothesis was accepted. The test results prove that the MIM-MEM method has an effect on increasing students’ motivation and Arabic learning outcomes.